Employee Retention and Organizational Performance in Uganda: A Case of Kabale District Local Government - Julius, Ngabirano (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate training in Partial Fulfilment of the Requirements for the Award of Master’s Degree in Business Administration of Kabale University, Uganda